MATHEMATICAL MODELLING AND OPTIMAL INTERVENTION STRATEGIES FOR MENINGITIS TRANSMISSION DYNAMICS - Ayodeji Sunday Afolabi; Abdulwahab Ridwan; Princess Chiamaka Uche (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2026)
Meningitis remains a major public health concern, particularly within the African meningitis belt, where recurrent outbreaks pose severe health and socio-economic challenges. The disease is transmitted through close contact and is driven by complex human-to-human dynamics. While vaccination campaigns and treatment programs are central to control efforts, limitations such as waning immunity and delayed case detection often reduce their long-term impact. In alignment with global health recommendations, integrated control approaches that combine prevention, vaccination, and timely treatment are increasingly being advocated. In this study, a novel deterministic nonlinear seven-compartmental model, SVECITR, is developed. The model’s validity is confirmed through positivity and boundedness analyses, and key thresholds such as the DFE and the , are derived using the next-generation matrix method. Stability analysis was also performed. The framework is extended into an optimal control problem using three time-dependent interventions: public health education, booster vaccine administration, and prophylactic chemoprophylaxis. Using Pontryagin’s Maximum Principle, optimal strategies are obtained, and numerical techniques are employed to simulate various intervention scenarios. Our results reveal that while dual interventions moderately reduce disease prevalence, the combined application of all three control measures resulted in the most substantial decline in transmission. Cost-effectiveness analysis, which employs the Incremental Cost-Effectiveness Ratio (ICER), Average Cost-Effectiveness Ratio (ACER), and Infection Averted Ratio (IAR), shows that combining booster vaccination and prophylactic chemoprophylaxis emerges as the most cost-effective option. These findings suggest that, in resource-limited settings, public health authorities should prioritize booster vaccination and chemoprophylaxis administration to curb the spread of meningitis while optimizing the use of available resources.